2011
DOI: 10.1128/aem.05956-11
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of As-Yet-Uncultured Soil Acidobacteria on Dilute Solid Media

Abstract: A growing number of Acidobacteria strains have been isolated from environments worldwide, with most isolates derived from acidic samples and affiliated with subdivision 1. We recovered 18 Acidobacteria strains from an alkaline soil, among which 11 belonged to the previously uncultured subdivision 6. Various medium formulations were tested for their effects on Acidobacteria growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 36 publications
(34 reference statements)
3
27
0
Order By: Relevance
“…The contrasting tendencies of pH preference displayed by different classes of Acidobacteria in this site were in agreement with some recent studies (Rousk et al, 2010;George et al, 2011;Foesel et al, 2014). Unlike most other phyla, Acidobacteria seemed to be unaffected by contamination levels that suggests a role as generalists in hydrocarboncontaminated soils (Mukherjee et al, 2013).…”
Section: Discussionsupporting
confidence: 79%
“…The contrasting tendencies of pH preference displayed by different classes of Acidobacteria in this site were in agreement with some recent studies (Rousk et al, 2010;George et al, 2011;Foesel et al, 2014). Unlike most other phyla, Acidobacteria seemed to be unaffected by contamination levels that suggests a role as generalists in hydrocarboncontaminated soils (Mukherjee et al, 2013).…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, differential abundance analysis revealed that Acidobacteria groups 1, 2 and 3 favoured low moisture levels, whereas the other Acidobacteria classes present at Gi-FACE favoured either medium or high moisture levels. The data from Gi-FACE, therefore, provide evidence of ecological distinctness for individual acidobacterial classes, which contributes to our knowledge of these poorly known, albeit abundant soil bacteria (Quaiser et al, 2003;Janssen, 2006;Jones et al, 2009;Castro et al, 2010, George et al, 2011Griffiths et al, 2011).…”
Section: Class Order Familymentioning
confidence: 83%
“…The isolation of bacteria from forest topsoil was described by Lladó et al (28) Cultivation proceeded for up to 15 weeks, because long-term culturing was previously demonstrated to yield slow-growing bacteria from nutrient-limiting environments (34). The strains were stored in a sterile 20% glycerol solution at Ϫ80°C and subcultured on GY-VL55 agar plates at 24°C.…”
Section: Methodsmentioning
confidence: 99%